Antimicrobial ciprofloxacina em efluente hospitalar: exposição ambiental, avaliação de risco e degradação através de processos avançados de oxidação - Vasconcelos, Tibiriçá Gonçalves (2006)
In the present study, the presence of the antimicrobial ciprofloxacin (CIP) in effluent from the first-aid clinic of the University Hospital of Santa Maria (PA-HUSM) and its degradation by advanced oxidation processes (AOPs) - photo-induced process (medium pressure Hg-lamp 125 W, batch recirculation reactor, pH 3), heterogeneous catalysis (medium pressure Hg-lamp 125 W, helicoidal tubular reactor, pH 3, 400 mg TiO2), ozonation and peroxone (450 mg O3 h-1, pH 9, semi-batch system, 500 mg H2O2 L-1 for peroxone) were investigated. Determination of the CIP concentration developed by high pressure liquid chromatography with fluorescence detection (HPLC-FLD) was measured before (P1) and after (P2) treatment system (cesspit and anaerobic filter), during 7 days. Measured environmental concentrations (MECs) were 19-155 μg L-1 (average: 65±45 μg L-1) and 32-99 μg L-1 (average: 54±21 μg L-1) in P1 and P2, respectively. In addition, risk assessment based on the MECs and ecotoxicity data from the literature was proposed. Using three different values of predicted no-effect concentration (PNEC), MECs/PNEC ratios between 4-1,980 were calculated. These risk quotients imply a high risk for a negative impact of CIP to aquatic environment and suggest that risk management is necessary. These quotients are 48-3,300-fold higher than those found in developed countries and mean a worse-case than the discussed wide world until now. Regarding the treatment of the effluent by AOPs, photo-induced degradation was slowest than the other processes: half-life (t1/2) during photo-induced of CIP was 2.5 h, while heterogeneous photocatalysis, peroxone and ozonation presented 20, 15 and 9 min, respectively. The best results obtained through ozonation were consequence of the higher reactivity of CIP with ozone than with radicalar species formed during the processes. However, about chemical oxygen demand (COD) and integrated absorbance, peroxone and heterogeneous photocatalysis (higher capacity for hydroxyl radical generation) were more effective than the photo-induced and ozonation processes (lower hydroxyl radical generation capacity). The metabolites formed during the processes demonstrated to be very similar. In addition, photo-induced degradation of CIP (medium pressure Hg-lamp 150 W, batch reactor) in environmental concentration of 0.1 mg L-1 (0.3 x 10-6 mol L-1) and pH 9 (NH4Cl/KOH) was studied. The first order rate constant and half-life were 1.56 ±0.11 x 10-2 s-1 (R2 > 0.999) and 44±7 s, respectively. The first formed metabolites were identified by HPLC-FLD and high pressure liquid chromatography with mass detection (LC-MS). Five compounds were qualitatively identified as probable metabolites and were not ready biodegradable by closed bottle test (CBT). They would be products from reactions of defluorination, decarboxilation and break of the piperazine ring. They have been already reported in the literature but under other conditions.